Information and communication technologies and health in low income countries : the potential and the constraints - Chandrasekhar, C.P. (2001)
Outlines the potential offered by technological progress in the information and communication technologies (ICTs) industries for the health sector in developing countries. Presents some examples of positive experiences in India and considers the difficulties in achieving the potential.